SHELL PROGRAMMING LANGUAGE BASICS (Web of Technology: Multidimensional Research Journal, 2025)
This article explores the basics of Shell programming language, its syntax, and role in system management. Practical problems such as variables, conditional statements, loops, and file handling are addressed using Shell scripting. The research results demonstrate that Shell scripting is an effective tool for system automation. The advantages and limitations of Shell scripting are analyzed, and recommendations are provided for programmers.